2017
DOI: 10.1113/jp273695
|View full text |Cite
|
Sign up to set email alerts
|

T‐type calcium channels contribute to NMDA receptor independent synaptic plasticity in hippocampal regular‐spiking oriens‐alveus interneurons

Abstract: Key points Regular‐spiking interneurons in the hippocampal stratum oriens exhibit a form of long‐term potentiation of excitatory transmission that is independent of NMDA receptors but requires co‐activation of Ca2+‐permeable AMPA receptors and group I metabotropic glutamate receptors.We show that T‐type Ca2+ channels are present in such interneurons.Blockade of T‐type currents prevents the induction of long‐term potentiation, and also interferes with long‐lasting potentiation induced either by postsynaptic tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 47 publications
3
21
0
Order By: Relevance
“…In the present study, Nicholson and Kullmann () clearly showed that NMDA receptor‐independent LTP induced by high‐frequency stimulation of afferent fibres in the presence of the NMDA receptor antagonist d ‐2‐amino‐5‐phosphonovaleric acid ( d ‐APV) in O/A interneurons paired with postsynaptic hyperpolarization was almost completely inhibited by T‐type Ca 2+ channel blockers, indicating that the Ca 2+ influx through T‐type Ca 2+ channels is another source of Ca 2+ required for LTP induction. It is known whether this type of Ca 2+ channels is abundantly expressed in hippocampal interneurons, and in fact, the authors explicitly demonstrated electrophysiologically that T‐type Ca 2+ channels were functional in O/A interneurons.…”
supporting
confidence: 55%
See 2 more Smart Citations
“…In the present study, Nicholson and Kullmann () clearly showed that NMDA receptor‐independent LTP induced by high‐frequency stimulation of afferent fibres in the presence of the NMDA receptor antagonist d ‐2‐amino‐5‐phosphonovaleric acid ( d ‐APV) in O/A interneurons paired with postsynaptic hyperpolarization was almost completely inhibited by T‐type Ca 2+ channel blockers, indicating that the Ca 2+ influx through T‐type Ca 2+ channels is another source of Ca 2+ required for LTP induction. It is known whether this type of Ca 2+ channels is abundantly expressed in hippocampal interneurons, and in fact, the authors explicitly demonstrated electrophysiologically that T‐type Ca 2+ channels were functional in O/A interneurons.…”
supporting
confidence: 55%
“…In a previous paper by the same group (Le Duigou & Kullmann, 2011), exogenous activation of group I mGluRs with postsynaptic hyperpolarization was shown to be sufficient to induce LTP in the absence of presynaptic activities in hippocampal interneurons. This finding is rather unexpected because it is unclear why hyperpolarization in addition to mGluR activation is required for this type of LTP.In the present study, Nicholson and Kullmann (2017) clearly showed that NMDA receptor-independent LTP induced by high-frequency stimulation of afferent fibres in the presence of the NMDA receptor antagonist D-2-amino-5-phosphonovaleric acid (D-APV) in O/A interneurons paired with postsynaptic hyperpolarization was almost completely inhibited by T-type Ca 2+ channel blockers, indicating that the Ca 2+ influx through T-type Ca 2+ channels is another source of Ca 2+ required for LTP induction. It is known whether this type of Ca 2+ channels is abundantly expressed in hippocampal interneurons, and in fact, the authors explicitly demonstrated electrophysiologically that T-type Ca 2+ channels were functional in O/A interneurons.…”
mentioning
confidence: 51%
See 1 more Smart Citation
“…Specifically, there are strong lines of evidence that the induction of bidirectional synaptic plasticity in the hippocampus is mediated by different calcium sources, with certain protocols requiring synergistic activation of multiple calcium sources (Brager & Johnston, ; Christie et al, ; Golding et al, ; Huber et al, ; Nishiyama, Hong, Mikoshiba, Poo, & Kato, ; Raymond, ). These studies show that plasticity induction is dependent on influx of calcium through NMDA receptors (Christie et al, ; Collingridge & Bliss, ; Collingridge, Kehl, & McLennan, ; Morris, Anderson, Lynch, & Baudry, ; Mulkey & Malenka, ; Nishiyama et al, ; Tsien, Huerta, & Tonegawa, ; Wang, Xu, Wu, Duan, & Poo, ), voltage‐gated calcium channels (Brager & Johnston, ; Christie et al, ; Christie, Schexnayder, & Johnston, ; Johnston, Williams, Jaffe, & Gray, ; Moosmang et al, ; Nicholson & Kullmann, ; Wang et al, ), store‐operated calcium channels (Baba et al, ; Garcia‐Alvarez et al, ; Majewski & Kuznicki, ; Majewski et al, ; Prakriya & Lewis, ) and receptors on the ER activated by metabotropic receptors on the plasma membrane (Huber et al, ; Jedlicka & Deller, ; Nishiyama et al, ; Padamsey, Foster, & Emptage, ; Verkhratsky, ). Additionally, voltage‐gated channels and their auxiliary subunits (Anirudhan & Narayanan, ; Brager, Lewis, Chetkovich, & Johnston, ; Chen et al, ; Chung, Ge, et al, ; Chung, Qian, et al, ; Johnston et al, ; Jung, Kim, & Hoffman, ; Kim et al, ; Lin et al, ; Lujan et al, ; Malik & Johnston, ; Nolan et al, ; Sehgal et al, ; Shah et al, ; Watanabe, Hoffman, Migliore, & Johnston, ) have also been shown to critically regulate the strength and direction of synaptic plasticity.…”
Section: Degeneracy At Multiple Scales In the Hippocampusmentioning
confidence: 99%
“…Specifically, there are strong lines of evidence that the induction of bidirectional synaptic plasticity in the hippocampus is mediated by different calcium sources, with certain protocols requiring synergistic activation of multiple calcium 16, 2017; sources (Brager and Johnston, 2007;Christie et al, 1996;Golding et al, 2002;Huber et al, 1995;Nishiyama et al, 2000;Raymond, 2007). These studies show that plasticity induction is dependent on influx of calcium through NMDA receptors (Christie et al, 1996;Collingridge and Bliss, 1987;Collingridge et al, 1983;Morris et al, 1986;Mulkey and Malenka, 1992;Nishiyama et al, 2000;Tsien et al, 1996;Wang et al, 2003), voltage-gated calcium channels (Brager and Johnston, 2007;Christie et al, 1996;Christie et al, 1997;Johnston et al, 1992;Moosmang et al, 2005;Nicholson and Kullmann, 2017;Wang et al, 2003), store-operated calcium channels (Baba et al, 2003;Garcia-Alvarez et al, 2015;Majewski and Kuznicki, 2015;Majewski et al, 2016;Prakriya and Lewis, 2015) and receptors on the ER activated by metabotropic receptors on the plasma membrane (Huber et al, 2000;Nishiyama et al, 2000;Verkhratsky, 2002). Additionally, voltage-gated channels and their auxiliary subunits (Anirudhan and Narayanan, 2015;Brager et al, 2013;Chen et al, 2006;Chung et al, 2009a;Chung et al, 2009b;Johnston et al,...…”
Section: Degeneracy In Calcium Regulation and In The Induction Of Synmentioning
confidence: 99%